Structure‐activity studies of peptidomimetics based on kinase‐inhibitory region of suppressors of cytokine signaling 1. Issue 5 (16th February 2018) - La Manna, Sara; Lopez‐Sanz, Laura; Leone, Marilisa; Brandi, Paola; Scognamiglio, Pasqualina Liana; Morelli, Giancarlo; Novellino, Ettore; Gomez‐Guerrero, Carmen; Marasco, Daniela
Abstract: Suppressors of Cytokine Signaling (SOCS) proteins are negative regulators of JAK proteins that are receptor‐associated tyrosine kinases, which play key roles in the phosphorylation and subsequent activation of several transcription factors named STATs. Unlike the other SOCS proteins, SOCS1 and 3 show, in the N‐terminal portion, a small kinase inhibitory region (KIR) involved in the inhibition of JAK kinases. Drug discovery processes of compounds based on KIR sequence demonstrated promising in functional in vitro and in inflammatory animal models and we recently developed a peptidomimetic called PS5, as lead compound. Here, we investigated the cellular ability of PS5 to mimic SOCS1 biological functions in vascular smooth muscle cells and simultaneously we set up a new binding assay for the screening and identification of JAK2 binders based on a SPR experiment that revealed more robust with respect to previous ELISAs. On this basis, we designed several peptidomimetics bearing new structural constraints that were analyzed in both affinities toward JAK2 and conformational features through Circular Dichroism and NMR spectroscopies. Introduced chemical modifications provided an enhancement of serum stabilities of new sequences that could aid the design of future mimetic molecules of SOCS1 as novel anti‐inflammatory compounds. Abstract :